FEEDING RULES EDUCATION AS AN EFFORT TO IMPROVE MOTHER’S KNOWLEDGE TO OVERCOME EATING PROBLEMS IN CHILDREN TODDLER AT DESA BANTERAN KECAMATAN SUMBANG: CASE REPORT - Sesilia Daima; Meivita Dewi Purnamasari; Lita Heni Kusumawardani (International Journal of Biomedical Nursing Review, 2024)
Introduction: Toddlers are the golden phase orgold period. In this phase, children will experience very rapid growth and development. Nutrition or nutrients are an absolute factor needed by the body in the growth and development process. Purpose: Therefore, this research aims to be an effort to overcome nutritional disorders in children by providing education feeding rulesor guidelines for feeding children. Methods: The research method used by the author uses a case study. The research subjects were mothers with toddlers who experienced nutritional problems. Conclusion: Providing education feeding rules in mothers with children under five who have nutritional problems, changes in knowledge have increased significantly. This can be seen from the difference in scores onpretest and posttest namely 33.3% to 83.3%.